(untitled) (Journal of Contemporary Philology, 2021)
In India, the prevalence of (Indian) English and code-switching between languages is not new. However, there has been a dearth of research that explores code-switching in Indian English (IE) within the genre of sociopolitical talk in Indian English tv talk shows. The current study is a part of a larger longitudinal study that analyzes code-switching patterns across the previous decade in Indian English tv talk shows and is the first in the series of follow-up studies. This study qualitatively examines an episode of an Indian English tv talk show to determine code-switching (CS) patterns and functions in IE. The study employed linguistic analysis, Meyerhoff’s (2007) accommodation theory, Sacks, Schegloff, and Jeferrson’s (1974) conversation analysis methodology, and a world Englishes framework to discover the forms, functions, and motivations of CS in an English matrix context. Findings confirm Si’s (2010) results that speakers preferred higher number of English alternations and insertions than Hindi code-switches, while Hindi-only turns were relatively few. Functions of analyzed code-switches also indicated intentions to reformulate, repeat, quote, connect with or diverge from other interlocutors, and generate emphasis in discourse. The study concludes with implications for Indian English and avenues for future research.